Confessions Of A Forty-Something F##k Up: Nell Stevens # 1 - Potter, Alexandra (New York : Harper, 2023)
"Nell Stevens' life is a mess. When her business goes bust and her fiancé with it, Nell's happy ever after in California falls apart and she moves back to London to start over. But a lot has changed since she's been gone. All her single friends are now married with children, sky-high rents force her to rent a room in a stranger's house, and in a world of perfect Instagram lives, she feels like a f**k up. Even worse, a forty-something f##k up. But when she lands a job writing obituaries, Nell meets the fabulous Cricket, an eighty-something widow with challenges of her own, and they strike up an unlikely friendship. Together they begin to help each other heal their aching hearts, cope with the loss of the lives they had planned and push each other into new adventures and unexpected joys. An international bestseller, this is a book for anyone who's ever worried their life isn't going to plan"--.
new book 2023 fall.
Keywords: Journalists; Life change events; Female friendship; Middle-aged women; Single women; Obituaries; Novels